IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) UNTUK MENINGKATKAN MUTU LULUSAN DI SEKOLAH DASAR (STUDI KASUS DI SDN 1 CITALANG KABUPATEN PURWAKARTA) - Wawan Kustiawan; Juandi Azi Wijaya; Tita Sumiarsih; Dinny Mardiana (STKIP Subang, 2026)
This research is motivated by the low quality of graduates in several elementary schools, which is caused by centralized educational management that is insufficiently responsive to local needs. The implementation of School-Based Management (SBM) is regarded as a strategic solution to provide broader autonomy to schools in managing resources to improve graduate quality. The purpose of this study is to identify supporting and inhibiting factors and to analyze the implementation of SBM in improving the quality of graduates at SDN 1 Citalang, Purwakarta Regency. Management encompasses planning, organizing, implementing, and controlling aimed at achieving organizational goals effectively and efficiently. According to George R. Terry, management is a distinct process consisting of planning, organizing, actuating, and controlling actions carried out to determine and achieve established objectives through the utilization of human and other resources. In the educational context, management becomes a key factor in ensuring the systematic and sustainable implementation of teacher professionalism development processes. This study employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participant observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of SBM at SDN 1 Citalang has been running quite effectively, as evidenced by increased participation of all school members and the school committee in decision-making, enhanced teacher professionalism, and optimized use of school-needs-based budgeting. The quality of graduates has improved, particularly in terms of basic academic abilities, independence, and discipline. This study recommends the need for continuous training on SBM for teachers and school committees, as well as strengthening periodic internal evaluations to maintain and improve the quality achievements of graduates.